2011
DOI: 10.1007/s12185-011-0843-6
|View full text |Cite
|
Sign up to set email alerts
|

Social outcomes and quality of life of childhood cancer survivors in Japan: a cross-sectional study on marriage, education, employment and health-related QOL (SF-36)

Abstract: Social outcomes and quality of life (QOL) of childhood cancer survivors (CCSs) remain unknown in Japan. We investigated these outcomes in young adult CCSs compared to those of their siblings in Japan, and analyzed the association between social outcome and SF-36 health survey subscale scores. Between 2007 and 2009, we performed a cross-sectional survey using self-rating questionnaires. We estimated social outcomes and health-related QOL by performing the SF-36 in each group: CCSs with or without stem cell tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 26 publications
3
48
5
2
Order By: Relevance
“…Previous studies on factors linked with childhood cancer survivors' unemployment have rarely explored the long-term effects as a potential determinant. However, developing physical late effects has been found to increase the risk of unemployment [16,19,20,29]. In contrast, we found no factor related to the survivor's history of AL to indicate a higher risk of unstable employment for the survivors in our study.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Previous studies on factors linked with childhood cancer survivors' unemployment have rarely explored the long-term effects as a potential determinant. However, developing physical late effects has been found to increase the risk of unemployment [16,19,20,29]. In contrast, we found no factor related to the survivor's history of AL to indicate a higher risk of unstable employment for the survivors in our study.…”
Section: Discussioncontrasting
confidence: 83%
“…Dieluweit et al reported a higher proportion of adolescent cancer survivors who were employed compared to an age-matched sample from the general population [20]. Nevertheless, most of the published studies found the employment rate to be lower among childhood cancer survivors compared with the controls [6,13,[15][16][17][18]29]. However, some of these studies include survivors of childhood brain and central nervous system cancers, and the difference in employment rate with the controls disappears when those types of cancers are excluded [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies of attained education level among survivors of all childhood cancers found that they had lower educational qualifications than the general population or a sibling comparison group, although some studies found no difference or even higher educational achievement among survivors . In a population‐based study in Great Britain, survivors of all childhood cancers had lower educational attainment than the general population (OR: 0.77, 99% CI: 0.68–0.87) .…”
Section: Resultsmentioning
confidence: 87%
“…Studies of the employment status of survivors of a broad range of childhood cancers in comparison with the general population or sibling comparisons had inconsistent findings . Seven studies observed higher unemployment rates among survivors, whereas five studies found similar unemployment rates . Studies with stratification by type of unemployment found that survivors were more likely to be unemployed due to illness or disability .…”
Section: Resultsmentioning
confidence: 94%
“…In fact, children are informed of their illness at the age of 15, on average, and in many instances younger children are not informed of the fact that they have cancer. Previous studies conducted in Japan on the same topic have reported on the mental health, anxiety, and adaptive process of children after discharge (12,13). The reality of outcomes has been determined, but relevant factors that will guide interventions and assistance have not been analyzed.…”
Section: Introductionmentioning
confidence: 99%